Magnetic resonance-based visualization of gene expression in mammalian cells using a bacterial polyphosphate kinase reporter gene. (February 2007) - Ki, Sewon; Sugihara, Fuminori; Kasahara, Koji; Tochio, Hidehito; Shirakawa, Masahiro; Kokubo, Tetsuro
Gene expression reporter systems, in which a promoter of interest is cloned upstream of a readily assayed reporter gene, have been developed and used extensively to study gene expression in prokaryotes and eukaryotes. Unfortunately, most of these systems cannot be used to assay gene expression in nonsuperficial tissues in living organisms. This study examines a novel reporter gene system based on the gene encoding Escherichia coli polyphosphate kinase (PPK), which can be used to monitor gene expression in mammalian cells. PPK catalyzes the synthesis of inorganic polyphosphate (polyP) from ATP, and because mammalian cells do not contain detectable levels of polyP, PPK activity can be measured in mammalian cells using 31 P-magnetic resonance spectroscopy or 31 P-magnetic resonance imaging. The ppk reporter gene system described here is noninvasive, does not require an exogenous substrate, and can potentially be used in internal tissues of living organisms.